Teaching and Learning German in the Philippines - Diederich, Matthias (Linguae et Litterae, 2010)
Exhaustive studies in contrastive linguistics have shown that in the field of language education the learner’s mother tongue is of great importance (Apeltauer 1997). It is crucial to take this in consideration when teaching a foreign language. For most Filipinos--who do not speak just one language, but several, including English--possession of English as a second language becomes both an advantage and disadvantage in learning foreign languages.